Programming Self-Assembled Materials With DNA-Coated Colloids - Zhang, Tianran; Lyu, Dengping; Xu, Wei; Mu, Yijiang; Wang, Yufeng (Frontiers in Physics, 2021)
Introducing the concept of programmability paves the way for designing complex and intelligent materials, where the materials’ structural information is pre-encoded in the components that build the system. With highly tunable interactions, DNA-coated particles are promising building elements to program materials at the colloidal scale, but several grand challenges had prevented them from assembling into the desired structures and phases. In recently years, the field has seen many significant progresses in tackling these challenges, which have led to the realization of numerous colloidal structures and dynamics previously inaccessible, including the desirable colloidal diamond structure, that are useful for photonic and various other applications. We review these exciting progresses, focusing in detail on how DNA-coated colloids can be designed to have sophisticatedly tailored surface, shape, patches as well as controlled kinetics, which are key factors that allow one to program in principle a limitless number of structures. We also share our view on how the field may be directed in future.